A scoping review of WeChat to facilitate professional healthcare education in Mainland China. Issue 1 (1st January 2020) - Luan, Hui; Wang, Miao; Sokol, Rebeccah L.; Wu, Shiyou; Victor, Bryan G.; Perron, Brian E.
ABSTRACT: Aim: WeChat is the most popular social media platform in mainland China, with over 1 billion active users. Although social media is widely used in professional healthcare education in western countries, research on WeChat-based education in healthcare in mainland China is disparate and not systematic. The current study seeks to address this gap. Method: A scoping review was conducted to systematically describe studies of WeChat use in professional healthcare education. A comprehensive search involving three international databases in English and Chinese literature was conducted in April 2019. Articles were retained in this study if they were original studies that used WeChat as a tool to facilitate healthcare education in mainland China. Results: 25 studies met the inclusion criteria and the majority of studies were either experimental or quasi-experimental. WeChat was used in both university settings and hospital settings. Hybrid education–which integrates WeChat education and face-to-face education–was more common in university settings, whereas hospitals used a combination of hybrid and WeChat-only strategies. Significant heterogeneity was observed regarding the type of accounts and methods for delivering content and facilitating online conversations. A majority of studies found positive outcomes with WeChat education. Conclusions: This scoping review addressed a large gap in knowledge about the usage of WeChat in professional healthcare education. Of the existing studies identified, we observed considerable promise for future practice. We provide additional suggestions for conducting future research involving patients and other helping professionals in healthcare education to expand the usage of WeChat.